LOGICAL TASKS AS A FACTOR FOR THE DEVELOPMENT OF LOGICAL-MATHEMATICAL SKILLS OF JUNIOR PUPILS - Долгое, Олег (Modern engineering and innovative technologies, 2019)
The article is devoted to the problem of development of logic and mathematical abilities of junior students by means of logic games. A system of variational logic and mathematical problems for the formation of interest of junior students in mathematics, l